2020
DOI: 10.20961/stjssa.v17i2.45130
|View full text |Cite
|
Sign up to set email alerts
|

Role and perspective of Azotobacter in crops production

Abstract: <p>Low nitrogen content in soil is usually overcome by chemical fertilization. After long application period, high-dose and intensive use of N fertilizers can cause ammonia volatilization and nitrates accumulation in soil. In sustainable agriculture, the use of bacterial inoculant integrated with nutrient management system has a role in soil health and productivity. Azotobacter-based biofertilizer is suggested as a chemical nitrogen fertilizer substitute or addition in crop production to improve availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…31 In relation to the biomass of Z. mays enhanced by A. vinelandii in soil impacted by 10,000 ppm of biostimulated GAS 60,000 ppm of VC, 40.81 g of AFW and 19.22 g of RFW were recorded, as well as 5.79 g of ADW and 2.59 g of RDW; statistically different numerical values at 7.43 g of AFW and 6.38 g of RFW, as well as with 0.96 g of ADW and 1.85 g of RDW of Z. mays without A. vinelandii in soil impacted by GAS biostimulated with the CFC/60,000 ppm from VC; and with 6.40 g of AFW and 6.54 g of RFW, as well as with 0.84 g of ADW and RDW of Z. mays without A. vinelandii in soil impacted by GAS biostimulated with CFE and the 30,000 ppm of VC; compared to: 39.25 g AFW, 18.73 g RFW, 4.49 g ADW and 2.07 g RDW from Z. mays in soil without GAS fed mineral solution or relative control. The fresh and dry weight of Z. mays enhanced with A. vinelandii in soil impacted by GAS, biostimulated with 60,000 ppm VC, where a decrease in GAS concentration was recorded and observed the healthy growth of Z. mays, 28 indicating that A. vinelandii al convert root exudates into phytohormones, 32 simultaneously with the hydrolysis of some aromatics of the GAS, which was evidenced by the decrease in the concentration detected at the end of the phytoremediation from 10,000 ppm to 500 ppm of GAS, to decrease the concentration to a value lower than the maximum accepted by NOM-138-SEMARNAT/ SSA1-2003, 3 for soil biorecovery, in contrast to what was observed in Z. mays cultivated in soil impacted by GAS without A. vinelandii in where the toxicity of hydrocarbons from the gas caused an abnormal growth of Z. mays.…”
Section: Resultsmentioning
confidence: 96%
“…31 In relation to the biomass of Z. mays enhanced by A. vinelandii in soil impacted by 10,000 ppm of biostimulated GAS 60,000 ppm of VC, 40.81 g of AFW and 19.22 g of RFW were recorded, as well as 5.79 g of ADW and 2.59 g of RDW; statistically different numerical values at 7.43 g of AFW and 6.38 g of RFW, as well as with 0.96 g of ADW and 1.85 g of RDW of Z. mays without A. vinelandii in soil impacted by GAS biostimulated with the CFC/60,000 ppm from VC; and with 6.40 g of AFW and 6.54 g of RFW, as well as with 0.84 g of ADW and RDW of Z. mays without A. vinelandii in soil impacted by GAS biostimulated with CFE and the 30,000 ppm of VC; compared to: 39.25 g AFW, 18.73 g RFW, 4.49 g ADW and 2.07 g RDW from Z. mays in soil without GAS fed mineral solution or relative control. The fresh and dry weight of Z. mays enhanced with A. vinelandii in soil impacted by GAS, biostimulated with 60,000 ppm VC, where a decrease in GAS concentration was recorded and observed the healthy growth of Z. mays, 28 indicating that A. vinelandii al convert root exudates into phytohormones, 32 simultaneously with the hydrolysis of some aromatics of the GAS, which was evidenced by the decrease in the concentration detected at the end of the phytoremediation from 10,000 ppm to 500 ppm of GAS, to decrease the concentration to a value lower than the maximum accepted by NOM-138-SEMARNAT/ SSA1-2003, 3 for soil biorecovery, in contrast to what was observed in Z. mays cultivated in soil impacted by GAS without A. vinelandii in where the toxicity of hydrocarbons from the gas caused an abnormal growth of Z. mays.…”
Section: Resultsmentioning
confidence: 96%
“…However, according to literature, Azotobacter sp. acts as a bio-stimulant and bio-fertilizer, which stimulates the plant’s growth by providing some metabolites; moreover, it synthesizes indole acetic acid, phytohormones, gibberellin, and cytokinin which further improve the photosynthetic machinery of plant, hence causing improved growth and yield ( Hindersah et al, 2020 ). Likewise, Rossi et al (2017) investigated the efficiency of cerium oxide nanoparticles (0 and 500 mgKg –1 ) through enhanced activity of photosystem II in soybean and also improvement in its biomass and physiological parameters through tolerating Cd (0, 0.25, and 1 mg Kg –1 ) stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, the increases in growth parameters were more pronounced in case of strain (A) as indicated from the significant increases in plant height, shoot and root fresh and dry weights which recorded the highest value compared to uninoculated control. Hindersah, et al (2020) reported that, as a biofertilizer, biostimulants, and bioprotectant, Azotobacter works to promote plant growth. Azotobacter uses nitrogen fixation as a method to make accessible nitrogen for root absorption.…”
Section: Effect Of Soil Inoculation With the Most Salinity Adapted Az...mentioning
confidence: 99%